2020
DOI: 10.21873/anticanres.14673
|View full text |Cite
|
Sign up to set email alerts
|

Using the Bolus in Post-mastectomy Radiation Therapy (PMRT): A National Survey on Behalf of the Italian Association of Radiotherapy and Clinical Oncology (AIRO) Breast Cancer Group

Abstract: Background/Aim: This study aimed to investigate the bolus practice among Italian radiation oncologists. Patients and Methods: In 2018, a survey on bolus application was sent to all members of the Italian Association of Radiotherapy and Clinical Oncology. Results: The survey was joined by 102 radiation oncologists. Not all respondents answered to every question. A 69.5% of 82 respondents used bolus in case of skin infiltration and 52 of 68 respondents (76.5%) applied it every day. Skin was included as part of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Bolus serves as a tissue equivalent material that shifts the 95-100% isodose towards the skin and subcutaneous tissue (depending on the thickness of bolus and subcutaneous tissue) [1]. The need for bolus for all breast cancer patients planned for PMRT has been questioned due to skin toxicity as seen in a number of studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], clinician surveys [21][22][23][24][25], and national guidelines [26]. All studies showed huge variability in terms of bolus indications and use, with no proven optimum regimen pertaining to thickness, schedule (i.e., daily, alternating days), bolus material, and RT planning characteristics (such as beam energy)…”
Section: Introductionmentioning
confidence: 99%
“…Bolus serves as a tissue equivalent material that shifts the 95-100% isodose towards the skin and subcutaneous tissue (depending on the thickness of bolus and subcutaneous tissue) [1]. The need for bolus for all breast cancer patients planned for PMRT has been questioned due to skin toxicity as seen in a number of studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], clinician surveys [21][22][23][24][25], and national guidelines [26]. All studies showed huge variability in terms of bolus indications and use, with no proven optimum regimen pertaining to thickness, schedule (i.e., daily, alternating days), bolus material, and RT planning characteristics (such as beam energy)…”
Section: Introductionmentioning
confidence: 99%
“…In PMRT patients, clinicians usually intend to treat the skin and typically prescribe the use of physical bolus (p‐bolus) to increase the superficial dose in the presence and absence of breast reconstruction 8 . Regimens for p‐bolus can become complicated and cause confusion among the staff, particularly for busy clinics.…”
Section: Introductionmentioning
confidence: 99%
“…In PMRT patients, clinicians usually intend to treat the skin and typically prescribe the use of physical bolus (p‐bolus) to increase the superficial dose in the presence and absence of breast reconstruction. 8 Regimens for p‐bolus can become complicated and cause confusion among the staff, particularly for busy clinics. While the use of p‐bolus in PMRT is itself a point of controversy in the community, 9 , 10 understanding the available tools to control the superficial dose is imperative to providing the best patient experience and outcomes.…”
Section: Introductionmentioning
confidence: 99%